2005
DOI: 10.1007/s10120-005-0343-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of peritoneal lavage cytology in gastric cancer in Singapore

Abstract: Positive peritoneal lavage cytology correlated well with advanced features of gastric cancer. It is an independent poor prognostic factor and the procedure should be routinely performed. Integration of lavage status into our current staging systems may serve as a guide for adjuvant therapeutic options to improve the survival of gastric cancer in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
1
35
2
3
Order By: Relevance
“…The present study also revealed that tumors with angiolymphatic invasion had a significantly higher rate of positive PWC. This result supports the theory of peritoneal carcinomatosis, which suggests shedding of cancer cells from both the serosal surface and the lymphatic system [13].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The present study also revealed that tumors with angiolymphatic invasion had a significantly higher rate of positive PWC. This result supports the theory of peritoneal carcinomatosis, which suggests shedding of cancer cells from both the serosal surface and the lymphatic system [13].…”
Section: Discussionsupporting
confidence: 89%
“…However, when the tumor invaded the serosa (pT3) and adjacent organs (pT4), the percentages of positive PWC were 19% and 73%, respectively. Previous studies also reported that serosal invasion was associated with a higher likelihood of cytological positivity [2,3,13,21,24]. It seems that the invasion of gastric serosa is a prerequisite for transperitoneal metastasis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Lee et al [7] in his study of 1072 patients showed 16% positive cytology. Bhatti etal [8] from Pakistan showed in their retrospective studies of 149 patients, 40% rate of positive peritoneal cytology obtained using laparoscopy. Unlike all this studies the rate positive peritoneal cytology was very high in our study (54%).…”
Section: Discussionmentioning
confidence: 99%